(untitled) (Jurnal Teknologi Industri Pertanian, 2012)
ABSTRACT This paper discusses the activated charcoal from jati (Tectona grandis L.f) sawdust used as catching agent of formaldehyde on plywood glued with urea formaldehyde. The activated charcoal was produced in a stainless steel retort with electrical heater at temperature of 8500C by using NH4HCO3 0.25 % as activating agent with reaction time of 90 minutes. To reduce formaldehyde emission from plywood, activated charcoal were added to urea formaldehyde adhesives at four levels i.e 0, 2, 4, 6 and 8 %. FTIR, XRD and SEM were used to evaluate the structure of activated charcoal. The results showed that the yield of activated charcoal was 53.11 %, moisture content 1.43 %, ash content 7.07 %, volatile matter 6.07 %, and fixed carbon 86.85 %. The adsorptive capacity of iodine 1196.6 mg/g, benzene 21.75 %, formaldehyde 48.12 % and methylene blue 319.18 mg/g and surface area 1183.4 m2/g. The quality of activated charcoal especially the adsorptive capacity of iodine has met the commercial standard requirement of the Japanese Standard. The structure of activated charcoal was polar, amorphous and macropore with pore diameter range from 1.3 – 1.6 m, degree of crystalinity 26.0 %, the height (Lc) and wide (La) were 2.47 and 13.42 nm. The number (N) of aromatics layer was 7.0.The free formaldehyde content of urea formaldehyde resin and the emission of formaldehyde from plywood decreased as the concentration of activated charcoal increased, and the bonding strength of plywood met the Indonesian and Japanese Standard requirement. Keywords: activated charcoal, jati, structure, iodine, formaldehyde, plywood